1973
DOI: 10.1002/jsfa.2740240305
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds of the genus pyrus. VI. Distribution of phenols amongst the various tissues of the pyrus stem

Abstract: Stems of Pyrus calleryana, P. ussuriensis and P . communis var. jaspoideae, from both current and previous year's growth, were sampled in January and March and the phenols in the bud, cork, green cortex, white phloem and xylem tissues were investigated. For the individual tissues there appeared to be very little difference between the phenols of current and previous year's growth. However, although some phenols, such as arbutin and vanilloylcalleryanin, occur throughout all tissues of both January and March st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Indeed, these results suggest that most compounds are in the core. In this regard, to the present date, it has been reported that specific phenolics could accumulate in particular tissues at particular times, while others could be considered almost ubiquitous [ 31 ]. Beyond the physiological facts governing the distribution of phenolics in specific tissues, cleaning up the broccoli stalks by removing the bark could give rise to new materials featured by specific composition (complex carbohydrates and/or lipoidal material) with positive/negative effects on the extractability of specific individual compounds [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, these results suggest that most compounds are in the core. In this regard, to the present date, it has been reported that specific phenolics could accumulate in particular tissues at particular times, while others could be considered almost ubiquitous [ 31 ]. Beyond the physiological facts governing the distribution of phenolics in specific tissues, cleaning up the broccoli stalks by removing the bark could give rise to new materials featured by specific composition (complex carbohydrates and/or lipoidal material) with positive/negative effects on the extractability of specific individual compounds [ 32 ].…”
Section: Resultsmentioning
confidence: 99%